The role of K.H. Muhammad Djunaid Sulaiman in the development of Islam in Bone - Sriwahyuni,; Nurul Hafizha Zakaria,; Zelvira, (Al-Hikmah, 2025)
This study aims to analyze the role of AGH. Muhammad Djunaid Sulaiman in the development of Islam in Bone. As one of the influential scholars, he is known for his commitment to spreading Islamic values ​​through the educational institutions he founded. The focus of this study is to examine the strategies he implemented and his contribution to the dynamics of Islam in the region. This study uses a historical method, by reconstructing and analyzing past events systematically and objectively. Data collection techniques are carried out through library studies by reviewing literature relevant to the problems and objectives of the study. The results of the study indicate that AGH. Muhammad Djunaid Sulaiman implemented four main strategies, namely: (1) direct preaching, (2) improving the economy of the Bone community, (3) utilizing personal assets for socio-political interests, and (4) broadcasting Islam through local languages ​​and literary works. This study contributes to enriching the treasury of local Islamic history, especially in understanding the strategic role of regional scholars in the spread of Islam through social, economic, cultural, and educational approaches. Penelitian ini menganalisis peran AGH. Muhammad Djunaid Sulaiman dalam perkembangan Islam di Bone. Sebagai salah satu ulama yang berpengaruh, AGH. Junaid Sulaiman dikenal karena komitmennya terhadap penyebaran nilai-nilai Islam melalui institusi pendidikan yang didirikannya. Penelitian ini bertujuan untuk menganalisis strategi yang diterapkan oleh AGH. Muhammad Djunaid Sulaiman dan bagaimana peranannya dalam perkembangan Islam di Bone. Dalam penelitian ini, digunakan metode penelitian sejarah yakni peneliti secara sistematis dan objektif merekonstruksi serta menganalisis peristiwa-peristiwa yang terjadi pada masa lampau. Penelitian ini menggunakan teknik pengumpulan data pustaka dengan mengumpulkan berbagai literatur yang relevan dengan permasalahan dan tujuan penelitian. Hasil penelitian ini mengungkap bahwa AGH. Muhammad Djunaid Sulaiman menjalankan strateginya melalui empat metode, yaitu metode dakwah, memperbaiki ekonomi masyarakat bone, mengamalkan harta untuk kepentingan politik dan sosial, serta menyiarkan Islam melalui bahasa lokal dan sastra. Sehingga implikasi dari penelitian ini adalah memperkaya kajian sejarah Islam lokal, khususnya peran ulama lokal dalam menyebarkan agama Islam melalui konteks sosial, ekonomi, budaya, dan pendidikan.